The destructive tendency of the State and capital in their relations with nature - Silva, Everton Melo da (Argumentum, 2024)
This article discusses the destructive relationship of the State and capital with nature. It considers the essence of the socio-metabolic reproduction of the capital system together with the political command of the State. Through a bibliographical review of authors from the Marxist tradition who discuss the foundations of capital and socio-environmental destruction, we analyse the totalising and destructive logic of capital, especially in times of structural crises since the 1970s, the appearance of the State in socio-environmental destruction and the outbreak of the “environmental issue” and its contemporary expressions. It concludes that this structural crisis has accentuated the fierce and corrosive character of capital and the State over nature seeking to extract natural resources to maintain the pace of capital accumulation that causes socio-environmental damage to nature and society.
Keywords: State; Capital; Destruction of nature; Structural crisis; Environmental issue